Dampak Kebijakan Moneter Terhadap Perekonomian Indonesia: Analisis Time-Varying VAR - Putri, Andra Alvioliza; Doni Satria (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This study aims to analyze the impact of monetary policy shocks in Indonesia over time using the Time-Varying Vector Autoregression (TV-VAR) approach. The main focus is to identify the effectiveness of monetary policy transmission channels, particularly the interest rate and credit channels. The analysis reveals that the effects of monetary policy shocks are dynamic and have evolved over time. The transmission of monetary policy through the interest rate channel appears to be more effective in influencing macroeconomic variables, especially in curbing inflation and economic growth. In contrast, the credit channel exhibits a relatively weak and insignificant response, indicating that the role of banking intermediation in supporting economic growth remains suboptimal. These findings highlight the importance of strengthening and optimizing the interest rate transmission mechanism as the primary instrument for conveying the monetary policy stance, particularly in maintaining price stability.